FACTORS ASSOCIATED WITH HIP INVOLVEMENT AND ITS IMPACT ON TREATMENT DECISION IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS; TREASURE EXPERIENCE - Ediboglu, E. Durak; Kalyoncu, U.; Solmaz, D.; Kasifoglu, T.; Tekgoz, E.; Bes, C.; Akar, S. (Elsevier, 2022)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 01-04, 2022 -- Copenhagen, DENMARK